Modulação colinérgica de comportamentos sociais em camundongos - Vinicius Elias de Moura Oliveira (2015)
Social behavior is essential for hierarchy, mating, territorial aggression, affiliation and parental care. Thus, the species survival depends of this behavior. However,so far, the molecular basis of social behavior has not been elucidated. Acetylcholine (Ach) is an important modulator of olfactory discrimination and social memory acquisition. Nevertheless, the role of the cholinergic system on social behavior, especially in the polarization between aggression and affiliation, has not been established. Thus, our aim was to evaluate the role of the cholinergic tonus on the modulation of social behavior, analyzing its implication for vasopressin (the pro-aggressive hormone). We verified that cholinergic hypofunction increased aggressive behavior. This phenotype was reversed by galantamine (GAL), acetylcholinesterase inhibitor. In these animals, aggression was dependent of AVP expression and vasopressinergic neurons activity in the hypothalamus (paraventricular, supraoptic, lateral and anterior nucleuses), bed nucleus of stria terminalis and ventral lateral septum. Interesting, we saw that na increase in ACh levels blocked the arising of aggression in isolated animals. Social isolation increases the choline acetyltranferase (ChAT) expression in the hypothalamus. On the other hand, hypercholinergic animals presented increases on affiliation. In conclusion, our results showed that oscillations on cholinergic tonus can modulate social behavior. Furthermore, aggressiveness induced by cholinergic hypofunction is dependent on vasopressinergic system activity.